Young Adults With Type 1 Diabetes and Their Perspectives on Diabetes-Related Social Media: Qualitative Study - Tara Maxwell; Lillian Branka; Noa Asher; Persis Commissariat; Lori Laffel (JMIR Diabetes)
Abstract BackgroundYoung adults with type 1 diabetes (T1D) often struggle with self-management and achieving target glycemic control, and thus, may benefit from additional support during this challenging developmental life stage. They are also some of the highest users of social media (SM), which may have some benefits to young people with T1D. ObjectiveGiven the potential of SM support for people with diabetes, we sought to use qualitative methods to explore the perceptions of diabetes SM posts to influence self-care and emotional state of young adults with T1D. MethodsA series of Instagram (Meta) posts were selected by a multidisciplinary team of T1D experts. Young adults aged 18‐25 years with T1D duration of 1 year or more were recruited from the clinic to participate in a 60-minute semistructured videoconferencing interview. First, they were queried about their SM use in general and specific to diabetes. Next, they reviewed 10 posts with the interviewer. For each post, perceptions and reactions were queried. Participants were asked about each post’s impact on their emotional state and potential influence on diabetes self-care. Finally, they were asked to comment on what the posts emphasized and how they felt after viewing the posts. Interviews were transcribed and coded using thematic analysis. The participants’ diabetes management information was extracted from the electronic health record. ResultsThere were 26 young adults who completed the study. Their mean (SD) age was 22.6 (SD 2.0) years, T1D duration 12.6 (SD 5.9) years, and glycated hemoglobin (HbA1c ConclusionsSM has the potential to help young adults with T1D feel a sense of community, seek and share objective and subjective thoughts and feelings about diabetes, motivate diabetes self-care, and positively affect emotional state. However, it may also have the potential to demotivate self-care and exacerbate negative emotional state with regards to diabetes.